The Elderly Care Response to COVID-19 : A Review of International Measures to Protect the Elderly Living in Residential Facilities and Implications for Malaysia - World Bank (World Bank, Washington, DC, 2020)
This note presents an international picture of measures in response to the COVID-19 pandemic specifically for the elderly living residential facilities as a particularly vulnerable setting. For this purpose, the note reviews information available from selected economies and international organizations and NGOs that have introduced guidance or actionable measures. The note argues that significant and proactive efforts in the areas of prevention, control, resources, coordination, management, reporting, communication, and planning are needed to safeguard the elderly living residential facilities (long-term care homes, residential care homes, nursing homes, welfare homes, etc.) in response to the spread of COVID-19. While many measures that have been introduced internationally are of wide relevance, the note also pays specific attention to implications for Malaysia. This may include the following areas for policy consideration: (a) strengthening the linkage between the elderly care response and the overall response; (b) issuing clear guidelines and operating procedures for all residential facilities; (c) mobilizing resources for prevention and control; (d) implementing consistent measures with government support for both licensed and unlicensed residential facilities; (e) strengthening coordination between the social sector and the health sector and between residential facilities, health agencies and hospitals; and (f) building capacities.